The emerging story of Sodium Valproate in British newspapers- A qualitative analysis of newspaper reporting. (October 2022) - Siriwardena, Sanjula; McAllister, Neil; Islam, Salma; Craig, John; Kinney, Michael
Highlights: Sodium valproate is a major cause of teratogenicity in the offspring of women with epilepsy. How understanding of sodium valproate was portrayed in the media is relatively unknown. Teratogenicity was the key theme discussed in relation to sodium valproate in printed media in the UK. Abstract: Background: Sodium valproate is a significant human teratogen. Newspapers are a potential source of useful public health information, but the extent to which concerns around valproate were presented to the public via newspapers has not been evaluated. Aim: To explore how sodium valproate has been portrayed by UK newspapers over the last several decades. Method: Thematic analysis of all newspaper articles up to July 2020 with key terms 'Valproate' and 'Epilim'. Articles were retrieved with LexisNexis. Temporal variation in thematic content was analysed. Results: 275 articles were identified for analysis. Teratogenicity was the key theme in 86% of newspaper articles, failure of duty of care of medical professionals to communicate the risks of valproate in 68%, improving its regulation with public health interventions in 51% and litigation against Sanofi who produce valproate in 31%. Reporting was minimal pre-2000 and peaked in the recent 5 years. Conclusion: Issues surrounding valproate have been covered by UK newspapers, with a predominant focus on its teratogenic effects.